Предмет: Математика, автор: Аноним

3,3a + (a-4)=

5a - (0,7a + 8)=

5,3b - (2b + 3)=

9,6b + (7 - 0,4b)=

2c - (9 - 5,1c)=

-5c + (13 - 6c)=

3(x - 7) + 5x=

5(4 - 3x) + 8x=

(y - 4) * 2 +10y=

(2y + 5) * 4 -11y=

4x + 2(0,5x + 3)=

6x -3(x - 7)=

Помогите пожалуйста!!!

Ответы

Автор ответа: OSA2201
0
4,3а-4
4,3а-8
3,3в - 3
9,2в+7
7,1с-9
с+13
8х - 21
20-7х
12у-8
-3у-8
5х+6
3х+21
Автор ответа: Kamilanm
0
1) 4,3а-4
2)4,3а-8
3)3,3b-3
4)9,2b+7
5)7,1c-9
6)-11c+13
7)8x-21
8)20-7x
9)12y-8
10)-3y+20
11)5x+6
12)3x
Автор ответа: Kamilanm
0
12)3x+21
Похожие вопросы